The religious experience of British philosopher Anthony Flew - Ali Mir, Ikhlas (Al-Adab Journal, 2024)
The research represented an introduction that clarifies the methodological contexts for the idea of ​​religious experience and some aspects of the biography of the philosopher Anthony Flew, and then the research came with two papers, the first: the absence of rationality in atheism, and the second: religious experience through the biography of the British philosopher Anthony Flew, as that philosopher tried to show  The rational methodology that he followed in his journey to faith, and the research ended with the conclusion and the results that investigated what was framed by that philosopher.